Synthesis and Primary Activity Assay of Novel Benitrobenrazide and Benserazide Derivatives - Karolina Juszczak; Wojciech Szczepankiewicz; Krzysztof Walczak (Molecules, 2024)
Schiff bases attract research interest due to their applications in chemical synthesis and medicinal chemistry. In recent years, benitrobenrazide and benserazide containing imine moiety have been synthesized and characterized as promising inhibitors of hexokinase 2 (HK2), an enzyme overexpressed in most cancer cells. Benserazide and benitrobenrazide possess a common structural fragment, a 2,3,4-trihydroxybenzaldehyde moiety connected through a hydrazone or hydrazine linker acylated on an N′ nitrogen atom by serine or a 4-nitrobenzoic acid fragment. To avoid the presence of a toxicophoric nitro group in the benitrobenrazide molecule, we introduced common pharmacophores such as 4-fluorophenyl or 4-aminophenyl substituents. Modification of benserazide requires the introduction of other endogenous amino acids instead of serine. Herein, we report the synthesis of benitrobenrazide and benserazide analogues and preliminary results of inhibitory activity against HK2 evoked by these structural changes. The derivatives contain a fluorine atom or amino group instead of a nitro group in BNB and exhibit the most potent inhibitory effects against HK2 at a concentration of 1 µM, with HK2 inhibition rates of 60% and 54%, respectively.